2022
DOI: 10.3389/fendo.2022.899731
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone alleviates non-alcoholic liver steatosis via activating the hepatic cAMP/PKA/CREB pathway

Abstract: Non-alcoholic fatty liver disease (NAFLD), hallmarked by liver steatosis, is becoming a global concern, but effective and safe drugs for NAFLD are still lacking at present. Parathyroid hormone (PTH), the only FDA-approved anabolic treatment for osteoporosis, is important in calcium-phosphate homeostasis. However, little is known about its potential therapeutic effects on other diseases. Here, we report that intermittent administration of PTH ameliorated non-alcoholic liver steatosis in diet-induced obese (DIO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…In vitro, cAMP signaling pathway inhibited palmitic acid-induced intracellular lipid accumulation in PTH1R-dependent manner. cAMP signaling pathway activation upregulated the expression of the genes involved in lipid beta-oxidation and downregulated the expression of the genes related to lipid uptake and de novo lipogenesis [50]. In this study, we found that the overlapping DEGs among the 1st, 3rd and 5th day were involved in cAMP signaling pathway, which was consistent with previous studies [51,52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In vitro, cAMP signaling pathway inhibited palmitic acid-induced intracellular lipid accumulation in PTH1R-dependent manner. cAMP signaling pathway activation upregulated the expression of the genes involved in lipid beta-oxidation and downregulated the expression of the genes related to lipid uptake and de novo lipogenesis [50]. In this study, we found that the overlapping DEGs among the 1st, 3rd and 5th day were involved in cAMP signaling pathway, which was consistent with previous studies [51,52].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the DEGs in the livers between treated with and without MnCl 2 on the 3rd and 5th day were involved in AMPK signaling pathway (Fig. 3B-C), which was consistent with previous ndings [47][48][49][50]. AMPK signaling pathway induced by dapagli ozin reduced oxidative stress and in ammation in vitro model of NAFLD [47].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding peptide hormones, parathyroid hormone (PTH), the only FDA-approved anabolic treatment for osteoporosis [ 125 ], is commonly utilized as a pharmaceutical agent for the treatment of osteoporosis [ 21 ]. Low calcium levels induce PTH production, which subsequently activates the Wnt-beta catenin pathway crucial for bone formation.…”
Section: Current Modifications Of Bone Repair Materialsmentioning
confidence: 99%
“…The expression of these genes lead to the activation of the cAMP/PKA/CREB pathway, and facilitates NAFLD steatosis. 108 NAFLD in pregnancy is a risk factor for maternal and child health. 109 In this context, PTH reduces insulin sensitivity and β-cell functions in pregnancy.…”
Section: Role Of Vitamin D In Diabetesmentioning
confidence: 99%